PENGARUH PRODUK DOMESTIK BRUTO, INFLASI DAN CAPITAL ACCOUNT TERHADAP NILAI TUKAR RUPIAH ATAS DOLLAR AMERIKA SERIKAT PERIODE TAHUN 2001-2014 - Wilya. R, Sherly; Putro, Tri Sukirno; Mayes, Anthony (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analyze the influence of the Gross Domestic Product, inflation and Capital Account to the exchange rate on the US dollar. Variables used in this study is the rupiah, gross domestic product, Inflation and Capital Account.This study was conducted in Indonesia and using multiple linear regression analysis to test the hypothesis using SPSS version 20. The type of data used are time series starting from the year 2001 to 2014. Simultaneous test results (F) 0.010 <0.05 indicates that GDP, inflation, and Capital Acccount simultaneously affect the exchange rate. While the partial test or (t) shows that GDP 3.082> 2.228 means that GDP affect the exchange rate and inflation 2.391> 2.228 means inflation variables affect the exchange rate, while the capital account -0.498 <2.228, which means no significant effect on the exchange rate. Additionally obtained adjusted R-square value was 56.6%. This means that 56.6% of the rupiah against the dollar exchange rate movements can be predicted from the three variables, while 43.4% is explained by other variables.Keywords: exchange rate, gross domestic product, inflation,and capital account.